(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Because of ever-increasing urbanization and a flexuous population, there has been an increasing call for the construction of tall buildings. Earthquakes are the bane of such tall buildings. Because earthquake forces are haphazard in nature and unpredictable, we want to develop engineering tools for studying systems under the influence of those forces. Thus, careful modeling of such earthquake loads is required in order to examine the behavior of the structure with a clear perspective of the harm that is expected. Examining the structure for different earthquake intensities, followed by exams for various criteria at each level, has become an essential exercise over the last two decades. [9]Earthquake-resistant design (ERD) of construction has advanced significantly since the preliminary thoughts took form in the early 20th century. The invention of accelerofigure and introduction of response spectrum are the crucial steps in the history of ERD. The other essential development was the know-how of ductility and hysteretic damping. Gradually, the earthquake-resistant design has advanced considerably in the form of capacity design, displacement based design, and performance-based design. Earthquakes cause varying degrees of shaking in different locations, and the damage caused to buildings in these locations is also unique. As a result, it is critical to build an earthquake-resistant structure that can withstand a certain level of shaking and absorb the impact of an earthquake. Because of the varying depths of earthquakes, identical magnitudes of earthquakes occur, resulting in varying destructive effects in various regions. As a result, the seismic behavior of buildings with comparable layouts must be understood under various earthquake intensities. It is critical to perform seismic evaluation of the structure using various available methods in order to determine seismic responses. [2]